THE RELATIONSHIP BETWEEN CHRISTIAN RELIGIOUS EDUCATION AND THE GREAT COMMISSION MATTHEW 28:19-20 - Rivosa Santosa; Nira Olyvia; Victor Deak (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Education is everything related to increasing knowledge in development that is not limited by space and time. Education has elements of planning, systematic implementation and clearly measurable objectives. Broadly speaking, education is to gain new and useful knowledge for personal life and social life. Christian Religious Education is an education that teaches about faith in Jesus Christ. Christian religious education is a subject that must be taken by Christian students in formal schools. Besides being carried out in formal schools, Christian religious education is also carried out through church programs. Religious education is believed to be able to equip students from an early age to become people of high moral character. The Bible is a source of Christian religious education which contains content and teaching and learning methods that can be practiced by believers today. The main purpose of Christian religious education is to bring students to meet God through Jesus Christ as Lord and Savior. Everyone who believes in Christ has a duty to carry out the great commission of proclaiming the work of salvation to others and teaching them to grow in Christ (Matt. 28:19-20). The Great Commission is a mandate given by God to all believers to introduce Christ to the world. In this study, the authors used descriptive qualitative research. The author describes the relationship between Christian religious education and the Great Commission of the Lord Jesus in Matthew 28:19-20 by using relevant sources through literature studies and relevant journals. This research provides a new contribution and perspective on the relationship between Christian religious education and the Great Commission